Integrating pollen and sedimentary DNA refines reconstructions of vegetation change through human settlement: a case study from Lake Waihau, Aotearoa New Zealand - Xun Li; Georgia Thomson-Laing; Marcus J. Vandergoes; Jamie D. Howarth; Susanna A. Wood (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Late Holocene climate variability and lake productivity change inferred from the remote alpine catchment of Lake Bright, New Zealand - Julian Eschenroeder; Christopher M. Moy; Sebastian Naeher; Marcus J. Vandergoes; Oliver Rach; Dirk Sachse; Rik Tjallingii; Jamie D. Howarth; Adelaine Moody; Xun Li; Claire Shepherd; Elizabeth Kennedy; et al. (Quaternary Science Reviews, 2026)

An alternative to landslide volume-area scaling relationships: an ensemble approach adopting a difference model to estimate the total volume of landsliding triggered by the 2016 Kaikōura earthquake, New Zealand - Katie E. Jones; Jamie D. Howarth; Chris I. Massey; Biljana Luković; Pascal Sirguey; Corinne Singeisen; Caleb Gasston; Regine Morgenstern; William Ries (Landslides, 2025)
Evaluating the influence of earthquakes on erosion, landscape evolution, and sediment-related hazards requires quantifying the number, location, and volume of co-seismic landslides following large earthquakes. Direct measurements of individual landslide volumes are difficult to accomplish and, as a result, rarely attempted. As an alternative, power-law scaling relationships between landslide volume and area—derived from global landslide inventories—are often used to estimate landslide volumes. The accuracy of the volume estimates derived from using these global scaling relationships remain untested and could be a source of significant uncertainty. Here, an ensemble method, adopting a pre- to post-event 2 by 2 m difference model covering an area of 6875 km 2 , has been developed to accurately estimate the volume of the > 30,000 mapped landslides triggered by the 2016 Mw 7.8 Kaikōura earthquake New Zealand. Our ensemble method estimates the total landslide volume for the Kaikōura earthquake to be 241 (+ 100/ − 69) M m 3 . This newly quantified total volume estimate of co-seismic landsliding was then compared to the total volumes estimated using globally and locally derived scaling relationships, which were found to underestimate the total landslide volume by up to 52%. As an alternative, we recommend that landslide volumes be estimated by sampling directly from high-quality empirical datasets of individual landslide volumes with similar triggering and physiographic settings.

Earthquake-triggered submarine canyon flushing transfers young terrestrial and marine organic carbon into the deep sea - Katherine L Maier; Catherine E Ginnane; Sebastian Naeher; Jocelyn C Turnbull; Scott D Nodder; Jamie Howarth; Sarah J Bury; Robert G Hilton; Jess IT Hillman (Earth and Planetary Science Letters, 2025)

Integrated onshore–offshore paleoseismic records show multiple slip styles on the plate interface, central Hikurangi subduction margin, Aotearoa New Zealand - Charlotte O. Pizer; Jamie D. Howarth; Kate J. Clark; Alan R. Orpin; Stephanie E. Tickle; Lorna J. Strachan; Philip Barnes; Sian Camp; Monique Mckeown; Emily Twort (Quaternary Science Reviews, 2024)

Lacustrine mass movements in active tectonic settings: Lake tsunami sources in New Zealand's South Island - Katie E. Hughes; Sean J. Fitzsimons; Jamie D. Howarth (Geomorphology, 2024)

Sedimentary ancient DNA reveals the impact of anthropogenic land use disturbance and ecological shifts on fish community structure in small lowland lake - Georgia Thomson-Laing; Jamie D. Howarth; Javier Atalah; Marcus J. Vandergoes; Xun Li; John K. Pearman; Sean Fitzsimons; Chris Moy; Adelaine Moody; Claire Shepherd; Nicholas McKay; Susanna A. Wood (Science of The Total Environment, 2024)

A paleoecological investigation of recent cyanobacterial blooms and their drivers in two contrasting lakes - Caitlin Wheeler; John K. Pearman; Jamie D. Howarth; Marcus J. Vandergoes; Katherine Holt; Steven A. Trewick; Xun Li; Lucy Thompson; Georgia Thomson-Laing; Mailys Picard; Chris Moy; Nicholas P. Mckay; et al. (Harmful Algae, 2024)

A taxonomy-free diatom eDNA-based technique for assessing lake trophic level using lake sediments - Rose Gregersen; John K. Pearman; Javier Atalah; Sean Waters; Marcus J. Vandergoes; Jamie D. Howarth; Georgia Thomson-Laing; Lucy Thompson; Susanna A. Wood (Journal of Environmental Management, 2023)

Characterizing carotenoids in cyanobacterial cultures – Opportunities and implications for paleolimnological studies - Jonathan Puddick; Sebastian Naeher; John K Pearman; Carrie D Page; Donato Romanazzi; Lena A Schallenberg; Jamie D Howarth; Marcus J Vandergoes; Susanna A Wood (Harmful Algae, 2023)

It's all in the mud - The use of sediment geochemistry to estimate contemporary water quality in lakes - Sean Waters; Javier Atalah; Lucy Thompson; Georgia Thomson-Laing; John K. Pearman; Jonathan Puddick; Jamie D. Howarth; Lizette Reyes; Marcus J. Vandergoes; Susanna A. Wood (Applied Geochemistry, 2023)

An integrated proximal-distal radiocarbon dating approach provides improved age constraints for a key Holocene tephra isochron - Charlotte O. Pizer; Jamie D. Howarth; Kate J. Clark; Colin J.N. Wilson; Stephanie E. Tickle; Jenni L. Hopkins; Jenny A. Dahl (Quaternary Science Reviews, 2023)

Paleo-diatom records reveal ecological change not detected using traditional measures of lake eutrophication - Rose Gregersen; Jamie D. Howarth; Javier Atalah; John K. Pearman; Sean Waters; Xun Li; Marcus J. Vandergoes; Susanna A. Wood (Science of The Total Environment, 2023)

Deterministic processes drive national‐scale patterns in lake surface sediment bacteria and eukaryotic assemblage composition - John K. Pearman; Janet Adamson; Georgia Thomson‐Laing; Lucy Thompson; Sean Waters; Marcus J. Vandergoes; Jamie D. Howarth; Susanna A. Wood (Limnology and Oceanography, 2023)
Biological communities within lake surface sediments play a vital role in biogeochemical cycling and ecosystem services. Knowledge on abundance‐occupancy patterns and assembly processes across large spatial scales and over multiple environmental gradients is limited, yet essential to aid in protection and restoration. In the present study, surface sediment samples were collected from 296 lakes across a wide spatial scale and covering multiple interacting environmental gradients including size, depth, altitude, and trophic state. A suite of physicochemical parameters were used to characterize the environmental conditions and bacterial and eukaryotic assemblages were determined using 16S and 18S rRNA metabarcoding. The majority (~ 55%) of amplicon sequence variants were only found in a single lake with eukaryotes having a more restricted distribution than bacteria. Deterministic processes were inferred to be dominant for both bacteria (78%) and eukaryotes (51%), with variable selection being especially important for bacteria (49%). Variation partitioning indicated that land use in the catchment, which is strongly related to trophic state, was the most important environmental factor in explaining the assemblage composition. This nationwide study across broad gradients provides new insights into the ecology of bacteria and eukaryotes in lake surface sediments and a platform to better understand the effects of multiple environmental stressors on lake sediment assemblages.